Prevalence and Serological Diagnosis of Relapse in Paracoccidioidomycosis Patients - Sylvestre, Tatiane Fernanda [UNESP]; Franciscone Silva, Luciane Regina; Cavalcante, Ricardo de Souza [UNESP]; Moris, Daniela Vanessa; Venturini, James [UNESP]; Vicentini, Adriana Pardini; Carvalho, Lidia Raquel de [UNESP]; Mendes, Rinaldo Poncio [UNESP] (Public Library Science, 2014)
A review of 400 clinical records of paracoccidioidomycosis (PCM) patients, 93 with the acute/subacute (AF) and 307 with the chronic form (CF), attended from 1977 to 2011, selected as to the schedule of release for study by the Office of Medical Records at the University Hospital of the Faculdade de Medicina de Botucatu - Sao Paulo State University - UNESP, was performed to detect cases in relapse. The control of cure was performed by clinical and serological evaluation using the double agar gel immunodiffusion test (DID). In the diagnosis of relapse, DID, enzyme-linked immunosorbent assay (ELISA) and immunoblotting assay (IBgp70 and IBgp43) were evaluated. Out of 400 patients, 21 (5.2%) went through relapse, 18 of them were male and 3 were female, 6: 1 male/female ratio. Out of the 21 patients in relapse, 15 (4.8%) showed the CF, and 6 (6.4%) the AF (p>0.05). The sensitivity of DID and ELISA before treatment was the same (76.1%). DID presented higher sensitivity in pre-treatment (80%) than at relapse (45%; p = 0.017), while ELISA showed the same sensitivity (80% vs 65%; p = 0.125). The serological methods for identifying PCM patients in relapse showed low rates of sensitivity, from 12.5% in IBgp70 to 65.0% in IBgp43 identification and 68.8% in ELISA. The sensitivity of ELISA in diagnosing PCM relapse showed a strong tendency to be higher than DID (p = 0.06) and is equal to IBgp43 (p = 0.11). In sum, prevalence of relapse was not high in PCM patients whose treatment duration was based on immunological parameters. However, the used methods for serological diagnosis present low sensitivity. While more accurate serological methods are not available, we pay special attention to the mycological and histopathological diagnosis of PCM relapse. Hence, direct mycological, cytopathological, and histopathological examinations and isolation in culture for P. brasiliensis must be appropriately and routinely performed when the hypothesis of relapse is considered.